Human Rights Protection System in China - Sun, Pinghua. author. aut Link
XXII, 366 p. 2 illus.
Keywords: In recent years, more and more scholars in the world have become interested in human rights issues in China. This book hopes to serve as a window through which its readers will gain a better view of the theory and practice of human rights protection in the Chinese context. The book systematically introduces the dynamic development and progress of human rights protection in China, attaching great importance to the first white paper on Human Rights in China; the statement “The state respects and guarantees human rights” included in the Constitution; and the National Human Rights Action Plan of China, then putting forth fundamental principles to achieve international human rights standards and specific measures to improve human rights protection standards in China. Further, the book discusses “Foundations of Human Rights Guarantees in Contemporary China,” “Human Rights, Culture and Their Reconstruction in the Chinese Context” and “Socialist Legal System with Chinese Characteristics.” The final chapter is dedicated to the topic of “Judicial Protection System of Human Rights in China.” In appendices, four important documents on human rights in China.